Perhitungan Shutdown Margin Teras NuScale Menggunakan OpenMC - Razaqiyanto, Hadi; Shafii, Mohammad Ali; Raflis, Helen (Jurnal Fisika Unand, 2023)
One of the important reactor safety parameters to study is the issue of shutdown margin (SDM). This study aims to obtain an effective safety design of the NuScale reactor in reviewing the SDM value parameter. SDM calculations are performed using OpenMC, which is a programming code based on the Monte Carlo method. OpenMC is an open source calculation code that has the advantage of access to modifications to the reactor core geometry design. The type of reactor used in this simulation is the NuScale Small Modular Reactor (SMR) which is a Pressurized Water Reactor (PWR) type of reactor. The NuScale core simulation was designed in accordance with the General Design Criterion (GDC), which is a core arrangement that has a Control Rod Assemblies (CRA) regulating bank (RB) and CRA shutdown bank (SB) and UO2 fuel with an enrichment of <4.9%. From the calculation results, the SDM value of NuScale is 17743 pcm. This NuScale core SDM value indicates that the NuScale reactor under study complied with the sufficient safety design limits for all power levels and operating modes.